Comparing GENEActiv against Actiwatch-2 over Seven Nights Using a Common Sleep Scoring Algorithm and Device-Specific Wake Thresholds. Issue 4 (4th July 2022) - Jenkins, Claire A.; Tiley, Lucy C. F.; Lay, Isabella; Hartmann, Jessica A.; Chan, Julia K. M.; Nicholas, Christian L.
ABSTRACT: Demonstrating inter-device reliability is essential to use devices interchangeably, and accurately integrate, interpret, or compare data from different actigraphs. Despite this, there is a paucity of comparative literature over a timeframe exceeding one night. The aims of this study were to determine an optimal wake threshold for GENEActiv and to evaluate the concordance between Actiwatch-2 and GENEActiv using a common algorithm (Phillips Respironics). Data were collected from 33 individuals (20 female) aged 20–35 years ( M = 25.33, SD = 4.69) across a total 213 nights. Participants wore both devices simultaneously and continuously for seven days. The sleep parameters of interest were: total sleep time, sleep efficiency, sleep onset latency, and wake after sleep onset. Exploratory analyses of sensitivity, specificity, overall accuracy, mean bias, and paired samples t-tests indicated an optimal wake threshold of 115 for GENEActiv, compared with Actiwatch-2 at the 40 (medium, default) threshold. Using these thresholds, sensitivity, and overall accuracy of GENEActiv were both good (86% and 78%, respectively), however specificity was relatively low (40%). There were no significant inter-device differences for any sleep parameters, and all absolute mean biases were small. Overall, the findings from this study provide the first empirical evidence to support the reliability of GENEActiv against Actiwatch-2 over multiple nights using a common algorithm with device-specific wake thresholds.